Human visceral afferent recordings: preliminary report. Issue 2 (28th October 2010) - Peiris, Madusha; Bulmer, David C; Baker, Mark D; Boundouki, George; Sinha, Sidhartha; Hobson, Anthony; Lee, Kevin; Aziz, Qasim; Knowles, Charles H
Abstract : Background: Conditions characterised by chronic visceral pain represent a significant healthcare burden with limited treatment options. While animal models have provided insights into potential mechanisms of visceral nociception and identified candidate drug targets, these have not translated into successful treatments in humans. Objective: To develop an in vitro afferent nerve preparation using surgically excised freshly isolated human colon and vermiform appendix-mesentery tissues. Methods: Non-inflamed appendix (n=18) and colon (n=9) were collected from patients undergoing right and left hemicolectomy. Electrophysiological recordings were made from mesenteric nerves and the tissue stimulated chemically and mechanically. Results: Ongoing neuronal activity was sparse and where units occurred peak firing rates were: colon (2.0±0.4 spikes/s, n=4) and appendix (2.4±0.6 spikes/s, n=9). Afferent nerves innervating the appendix responded with a significant increase in activity following stimulation with inflammatory mediators (73±10.6 vs 3.0±0.3 spikes/s, n=6, p<0.001, inflammatory mediator vs baseline) and capsaicin (63±15.8 vs 2±0.3 spikes/s, n=3, p<0.001, capsaicin vs buffer). Afferent nerves innervating the colon responded with increased activity to blunt probing of the serosal surface. Conclusions: This first-in-human study demonstrates afferent nerve recordings from human gut tissue ex vivo and shows that tissue may be stimulated both chemically and mechanically to study neuronal responses. Collectively, the results provide preliminary evidence to validate this in vitro human tissue model as one that may aid future disease mechanistic studies and candidate drug testing.